On Controlling Power Ramping and Output of Grid-Connected Rooftop Solar PV Using Battery Energy Storage System - Apichai Saipet (2019)
© 2019 IEEE. This work involves a control mechanism to reduce power ramping of grid-connected rooftop solar photovoltaic (PV) system. It is proposed to employ battery energy storage system to compensate PV output so that power to grid can be maintained with allowable tolerance. The optimum size of battery can be determined in accordance with setting target value of power to grid. The proposed method has been tested with a 5-kWp rooftop solar PV installed in Lampang, Thailand. The dataset is taken from representative weeks in January, April, August, and October. The dataset is measured and averaged every 5, 10, and 30 minutes. It is found that the optimum size of BESS is sensitive to the representative week (season) and the measured interval of power ramping.